The approach to coaching student teams in competitive sports, both amateur and professional, in the realm of sports - Rodin A.V. ,; Ryzhkin N.V. ,; Nemtseva E.V. ,; Polin R.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretically, to create and substantiate a plan for training student teams in competitive sports, both at the amateur and professional level. Methods and structure of the study. The methods employed were theoretical and sociological research methods, as well as strategic planning. The theoretical methods included: studying specialized scientific and methodological literature and regulatory documents; constructing a model of the subject; employing the structural and functional approach; describing and comparing; analyzing theoretical solutions and verifying the feasibility of resolving contradictions. The sociological method involved conducting an expert survey among 48 professionals from higher education institutions, who were asked to share their insights on the strategic directions for training student sports teams in competitive sports. The strategic planning method involved conducting a SWOT analysis, which involves identifying the factors within and outside the environment of the subject under study. Results and conclusions. From a managerial perspective, the crafted strategy encompasses objectives, milestones, and anticipated outcomes. Through the application of theoretical and sociological research techniques, as well as strategic planning, the elements of a comprehensive management plan for preparing student teams in competitive sports within the framework of amateur and professional sports have been devised and validated.